THE LEGAL CERTAINTY ON CHILDREN'S PERSONAL DATA: REALIZING LEGAL PROTECTION ON SOCIAL MEDIA - Regina Kartika Sari; Didik Endro Purwoleksono; Amira Paripurna (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
This research focuses on legal certainty regarding the formulation of children's personal data in the PDP Law and legal protection efforts for children's personal data on social media. This research is a normative legal research with a concept and statutory approach. The results of the study show that the formulation of children's personal data in positive law actually creates legal uncertainty so that it has an impact on the implementation of legal protection related to children's personal data requiring further regulations and guidelines. Legal protection efforts for children's personal data on social media can be carried out preventively and repressively. Preventively, legal protection for children's personal data on social media is carried out by involving the role of parents, society, and the state through the establishment of special institutions that provide an understanding of the importance for children to protect and understand the benefits of personal data. Repressively, legal protection for children's personal data on social media is carried out by prioritizing the aspect of compensation if the child's personal data is misused which harms the child's personality and is oriented towards criminal sanctions as determined in laws and regulations.